Ishophloroglucin A Isolated from Ishige okamurae Protects Glomerular Cells from Methylglyoxal-Induced Diacarbonyl Stress and Inhibits the Pathogenesis of Diabetic Nephropathy - Chi-Heung Cho; Min-Gyeong Kim; Bomi Ryu; Sang-Hoon Lee (Marine Drugs)
Ishige okamurae (I. okamuare), an edible brown alga, is rich in isophloroglucin A (IPA) phlorotannin compounds and is effective in preventing diseases, including diabetes. We evaluated its anti-glycation ability, intracellular reactive oxygen species scavenging activity, inhibitory effect on the accumulation of intracellular MGO/MGO-derived advanced glycation end products (AGE), and regulation of downstream signaling pathways related to the AGE–receptor for AGEs (RAGE) interaction. IPA (0.2, 1, and 5 μM) demonstrated anti-glycation ability by inhibiting the formation of glucose-fructose-BSA-derived AGEs by up to 54.63% compared to the untreated control, reducing the formation of irreversible cross-links between MGO-derived AGEs and collagen by 67.68% and the breaking down of existing cross-links by approximately 91% (p < 0.001). IPA protected cells from MGO-induced oxidative stress by inhibiting intracellular MGO accumulation (untreated cells: 1.62 μg/mL, MGO treated cells: 25.27 μg/mL, and IPA 5 μM: 11.23 μg/mL) (p < 0.001) and AGE generation and inhibited MGO-induced renal cell damage via the downregulation of MGO-induced RAGE protein expression (relative protein expression levels of MGO treated cells: 9.37 and IPA 5 μM:1.74) (p < 0.001). Overall, these results suggest that IPA has the potential to be utilized as a useful natural agent for the prevention and management of AGE-related diabetic nephropathy, owing to its strong anti-glycation activity.